A case study of a series of process writing workshops for teachers of English as a second language - Claude, Marianne (Rhodes University, Faculty of Education, Department of Education, 1994)
The case study, which is described in this thesis, is concerned with two aspects of second language teaching and learning, namely process writing and 'teacher development'. Ten Zulu speaking, English second language teachers in Durban, Natal, participated in a series of process writing workshops. Before the workshops, they were given opportunities to reflect, in interviews, upon their own past and present writing practices. After the workshops there were follow-up interviews to elicit their further understanding of what is involved in writing. The workshop materials were compiled and written by the researcher. The aims of the research project were, in summary, the following: to let the teachers, who are teachers of writing in their classrooms, become participating writers themselves; to make the process writing workshops be a reflective activity through which the participants would develop as teachers. The entire case study is positioned within critical theory, as a philosophical framework, in which the teachers' reflections upon their writing experiences is seen as emancipatory practice. The research project was small scale and predominantly qualitative. A narrative, 'explanation-building' analysis of the entire findings forms the major part of the thesis. The writing workshops gave the teachers in this study occasion to experience process writing; furthermore they were enabled to reflect in detail on their experiences. It is suggested that teacher training colleges and in-service courses incorporate the 'writing workshops for teachers ' concept, as an activity for growth and development. Further research may take the form of long term action research into how teachers who have attended such workshops implement the insights they have gained in their classrooms.
Keywords: English language -- Study and teaching -- South Africa -- Foreign speakers; English language -- Writing